Congenital Defect in the Musculature of the Stomach with Spontaneous Rupture in a Newborn Infant - Zaimi Zet; Sadikin Darmawan; Darmawan Kartono (Indonesian Pediatric Society, 1974)
In this communication a case ofspontaneous gastric perforation dueto congenital defect in the gastricmusculature, proven by histologicalexamination, will be reported.